Quantifying bird damage to wine grapes in the Western Cape of South Africa : a questionnaire-based approach - Dignon, Niki (Department of Biological Sciences, 2015)
Bird-wine grape damage is a globally acknowledged problem that has been the subject of considerable research in many wine growing regions. However, despite the Western Cape of South Africa being a major wine grape growing region, very little research has quantified bird damage in this region and very little is known about the extent of the problem. This research aimed to quantify bird damage to wine grapes in four grape growing regions of the Western Cape, through questionnaires. It also aimed to determine the factors that might explain the patterns of damage observed. 102 questionnaires were sent to the wine farms, and 52 were returned. Of the respondents, 71% reported bird grape damage. The amount of damage per wine farm ranged between 0% and 15% of the total rows of vines across a farm. When exploring the factors associated with whether a wine farm experienced bird damage, it was found that the border habitat of a farm was a significant factor. The composition of the border habitat greatly influenced the probability of bird damage. The PCA showed that tall trees, Fynbos and residential areas specifically increased the probability of bird damage. Within farms that experienced damage, it was found that in different vineyard blocks the areas closer to the edge of a vineyard and to trees were significantly more susceptible to bird damage. The most common reported damage-causing bird species were Red-Winged Starlings (Onycognathus morio) and White-Eyes (Zosterops lateralis). Damage was reported to occur mostly one month before harvest and at harvest time. This research provides a baseline for understanding the nature of bird damage in these regions and will aid future quantitative studies aimed at the management of the problem.